Horn, or The Counterside of Media - Schmidgen, Henning (Book collections on Project MUSE., 2022)
"Our daily dealings with media are characterized by a remarkable turn to the tactile. In practically all places, at practically all times, we touch and handle media devices. Conversely, these devices touch and scan us-and increasingly so: from pressure sensors in car seats and motion detectors in front of automatic doors to body scanners, smart phones, and fitness trackers. To this development, Horn, or The Counterside of Media responds by considering a substance and surface that is an exemplary "medium." Horn stands for a natural substance but also an artificial object. It constitutes a boundary between interior and exterior, while functioning as decoration and ornament, shield and tool. From Rebekka Horn, Salvador DaliÌ, and William Kentridge to Sigmund Freud, Walter Benjamin and Marshall McLuhan, this book enters into a creative dialogue with artists, scientists, and media philosophers that have dealt with animal horns, memory cones, musical instruments, and rhinoceroses. Presenting their respective contributions in a lavishly illustrated "fictitious exhibition," it unfolds a critical panorama of our tactile culture in which the counterside of media is clearly recognized and respected"--